Work-family interactions: experiences of underground mine workers at Unki in Shurugwi - Goredema, Melissa (Midlands State University, 2017)
The study explored the lived experiences of underground mine workers at Unki in Shurugwi special attention being on their work-family interaction. The developing portrayal of double worker families, single-parent families and families with senior care obligations, the overflow of women into non-conventional occupations and employments and the expanded association of men in the family area are quite recently a contributing factor of the progressions that have affected family structures. Using a qualitative descriptive research the researcher collected data from a sample of 13 participants. Data was obtained using semi-structured interviews. The researcher sorted the gathered information in thematic categories and a number of subthemes emerged, work-family conflict, family-work conflict, experiences in the working environment, interaction between work and home life, social life and well-being, personal aspects, work aspects, personal strategies and organizational strategies. These helped to further explore and answer formulated research questions. Findings of the research indicated that despite the efforts put by participants to separate the family and the work domain, the two remain correlated domains that are difficult to separate. And thus failure to sustain a balance between the home and family sphere remains the major source of physical and psychological strain for both male and female participants in the mining industry.